Endodontic treatment in geriatric patients - Andang, Milly Armilya; Achiar, Kurniasri Amas (Universitas Padjadjaran, 2007)
With the increased number of geriatric population, it is predicted that the need for dental treatment also increases. The needs for esthetic factors and function of geriatric patient are maybe similar to young patient. The number of geriatric patients who refuse dental extraction is increasing if there are still other alternative. They can be more convinced when the clinician said that the dental disease experienced is a focal infection so that the loss of the tooth can be accepted as the best option. But if it is possible, they will prefer endodontic treatment, because they want to keep their teeth according to the treatment plan or based on patient's request, as a less traumatic alternative compared to extraction.Endodontic treatment consideration for geriatric patient is quite similar to younger patients. The technique is also the same, although the problem may be bigger. The problem or obstacle that may arise in endodontic treatment for geriatric patient relates to the visit duration, problems during x-ray, problems in defining root canal location, vertical root fracture, and in some cases, decreased pulp tissue recovery ability. Due to the fact that the challenge is quite big, the success of endodontic treatment in geriatric patients needs to be considered. This paper will explain the endodontic treatment prognosis for geriatric patients.